Size-specific dose estimates for adult abdomen-pelvis computed tomography examinations in Johor - Bahrud Din, Nur Ashiqin (2017)
Accurate dose monitoring in computed tomography (CT) is important as CT provides high radiation exposure to the patient compared to other medical imaging modalities. The determination of size-specific dose estimate (SSDE) which takes into account the patient thickness has further facilitated radiation dose calculation in medical field. Present study has been conducted to determine firstly the difference between the average patient size and polymethymethacrylate phantom size, secondly the effects of various patient dimensions on the SSDE, and finally to verify the relationship between the SSDE and the volume CT dose index (CTDIvol), as well as that of between the SSDE and the patient size. One hundred abdomen-pelvis CT images have been utilized for coefficient of variation (CV) analysis using different patients’ thickness measurements. Descriptive statistics and Mann-Whitney test have been used to obtain the significant difference, p values. Simple linear regression model was plotted to determine the correlation between the SSDE and CTDIvol, as well as that of between the SSDE and patient’s thickness by referring to the summation of anterior-posterior and lateral (AP+Lateral) diameter. Routine abdomen-pelvis protocols considered in this study are in agreement with guidelines with a mean SSDE and CTDIvol of 15.5 ± 4.1 mGy and 11.4 ± 4.6 mGy, respectively. The SSDEs measured on the axial image and localizer radiograph show no significant difference, while the SSDEs derived from AP+Lateral diameter show a lower CV compared to other size descriptors, thus the latter is recommended to be used in the future SSDE calculation. Results show that the SSDE provides a better measure of the patient radiation dose value than the CTDIvol. It reduces the underestimation and overestimation problems of using phantoms in calculation of the CTDIvol. In conclusion, a promising approach using the SSDE as a measure of patient radiation dose can provide accurate dose estimation in clinical study compared to other approach based on the CTDIvol.